Passive small scale electric power generation using thermoelectric cells in solar pond. (15th December 2016) - Ding, L.C.; Akbarzadeh, A.; Date, Abhijit; Frawley, D.J.
Abstract: Solar ponds have been widely utilised in providing low grade heat needed for industrial processes and for heating applications <100 °C. In this paper, a small scale passive electric power generation unit was devised for generating electricity from the heat available in the solar pond. The power generation unit proposed operates without the use of a pump and involves no moving parts. The design of the power generation unit was finalised after performing a comprehensive theoretical study on the possible geometrical arrangements. The power generation unit was fabricated and tested experimentally. The power generation unit consists of 120 commercially available thermoelectric cells accommodated in the outer and inner layers of this dual layer power generation unit. The power generation unit had produced a maximum power of 40.8 W under the condition of T h = 99 °C. Under the normal operation of solar pond, the lower convective zone will have a temperature that lies within in the range of 40 °C –80 °C. Thus, maximum output in the range of 19.5 W–27.4 W is more realistic for the system proposed with the heat to electric conversion efficiency ranges between 0.37%–0.68%. Highlights: A passive power generation unit coupled with a solar pond using TECs is presented. The power generation unit is fabricated and tested to demonstrate the concept. Method of improving the power generation per volume is introduced.